2019
DOI: 10.2298/tsci161110030s
|View full text |Cite
|
Sign up to set email alerts
|

Improving thermal performance of micro-channel electronic heat sink using supercritical CO2 as coolant

Abstract: Original scientific paper https://doi.org/10.2298/TSCI161110030SIn view of increasing tendency of power density of electronic systems, cooling performance improvement of micro-channel heat sink is an emerging issue. In the present article, supercritical CO 2 is proposed as a heat transfer fluid in micro-channel heat sink for power electronics cooling. Energetic and exergetic performance analyses of micro-channel heat sink using supercritical CO 2 have been done and compared with conventional coolant, water. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…This gives a preliminary insight as to which coolants are better for use in the AWG system's heat sink. The papers which used the Al2O3/H2O Nanofluid, Transcritical CO2, Supercritical CO2 coolants for their experiments, did not provide such data for analysis [26][27][28][29][30].…”
Section: Coolantmentioning
confidence: 99%
See 2 more Smart Citations
“…This gives a preliminary insight as to which coolants are better for use in the AWG system's heat sink. The papers which used the Al2O3/H2O Nanofluid, Transcritical CO2, Supercritical CO2 coolants for their experiments, did not provide such data for analysis [26][27][28][29][30].…”
Section: Coolantmentioning
confidence: 99%
“…The TiO2/H2O nanofluid's dynamic viscosity was not provided and thus, it cannot be concluded from this data whether it is a more suitable coolant than the Galinstan. [26,30] (c) The required pumping power of supercritical CO2 is plotted against the thermal resistance [30].…”
Section: Coolant Type Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that thermal disintegration may dominate classical mechanical breakup when the fluid temperature close to the pseudo-boiling point. More extensive numerical investigations of the state of knowledge on supercritical mixing and combustion are available in literature [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…S-CO 2 also has gas characteristics, low viscosity, strong fluidity, low cycle loss of the system, and there is no phase transition in the cycle. S-CO 2 also has the characteristics of non-toxicity, non-flammability, good chemical stability, environmental friendliness and low cost [1][2][3]. Another important feature of S-CO 2 Brayton cycle is its high efficiency in large temperature range.…”
Section: Introductionmentioning
confidence: 99%